b - Becker, Joshua (b, 2016)
One of today's most influential minimalist advocates, Joshua Becker used to spend his days accumulating more and more. But then he realized his possessions were not only failing to make him happy, they were actually keeping him from the very things that do. Instead of bringing fulfillment, they brought distraction. In The More of Less, Joshua helps you recognize the life-giving benefits of owning less; realize how all the stuff you own is keeping you from pursuing your dreams; craft a personal, practical approach to decluttering your home and life; recognize why you buy more than you need; discover greater contentment, less envy, and more joy; experience the joys of generosity; and learn why the best part of minimalism isn't a clean house, it's a full life. It's time to own your possessions instead of letting them own you. After all, the beauty of minimalism isn't in what it takes away. It's in what it gives.
Keywords: Simplicity -- Christianity. -- Religious aspects; Consumption (Economics) -- Christianity. -- Religious aspects; Business & Economics -- Personal Success